Grenzüberschreitende Daseinsvorsorge in der Euregio Maas-Rhein. Was kann die Euroregion Pro Europa Viadrina lernen? - Unfried, Martin (Grenzüberschreitende Daseinsvorsorge. Stand und Perspektiven in europäischen Verflechtungsräumen, 2025)
Abstract: „Die euregionalen Partner in der Euregio Maas-Rhein, am Dreiländereck Deutschland/Niederlande/Belgien, haben in den letzten Jahrzehnten viel Erfahrung gesammelt beim Aufbau von Netzwerken im Bereich der öffentlichen Dienstleistungen. Der Artikel stellt wesentliche Netzwerke vor, wobei ausführlicher eingegangen wird auf die Entwicklungen im Bereich der Notfallrettung und der Gesundheitsversorgung, des öffentlichen Nahverkehrs und der Wohnungsmarktpolitik.“
Keywords: Euregio Maas-Rhein; Medizinische Versorgung; Rettungswesen; Wohnungsmarkt; Wohnungspolitik; Öffentlicher Personennahverkehr

„Gemeinsame Ordnungen“ oder „Grenzen“ - Historiker und der Begriff des Rheinlandes vor dem Ersten Weltkrieg. Justus Hashagen (1877–1961) im Kontex - Mölich, Georg (Les pays de l'entre-deux. Übergangsräume - Grenzregionen - Konfliktzonen. Mit Beiträgen der Jahrestagung 2019 in Saarbrücken, 2021)
Keywords: Rheinland

Partnerschaft der kurzen Wege. Fünfzig Jahre Jumelage zwischen Wegberg, Echt (NL) und Maaseik (B) - Pietsch, Folkmar (Heimatkalender des Kreises Heinsberg, 2021)
Keywords: Echt (Provinz Limburg, Niederlande); Maaseik; Städtepartnerschaft; Wegberg

The Bottom-Up Approach. Experiences with the Impact Assessment of EU and National Legislation in the German, Dutch and Belgian Cross-Border Regions - Unfried, Martin; Kortese, Lavinia Susan Josephine; Bollen-Vandenboorn, Anouk (Territorial Impact Assessment, 2020)
Aus den Verlagsangaben: „Considering the myriad cross-border regions that the EU counts, it is impossible for the European Commission to map detailed territorial cross-border effects in all of the EU’s border regions for the impact assessments it conducts. National governments also face obstacles when seeking to cohesively integrate cross-border impact assessments in the existing frameworks that they use to assess the impact of new legislative, policy and enforcement measures. Even border regions or cross-border entities themselves face challenges in implementing impact assessments in their own territories. Despite the need for structural analyses of the border effects of newly adopted legislation and legislation under review, in terms of policy and enforcement, there are issues regarding the availability of academic resources, relevant tools and know-how. For the last couple of years, researchers from Maastricht University have been assessing as a bottom up exercise the potential effects of legislative proposals on the specific Dutch/German and Dutch/Belgium cross-border territories. This article presents the methodology used and the experiences gained from 2016 to 2019 by highlighting a number of interesting cases. It also offers future ideas for conducting similar “bottom-up” regulatory territorial impact assessments in cross-border regions.“
Keywords: Euregio Maas-Rhein; Gesetzgebung; Grenzgebiet; Wirtschaftsbeziehungen; Wirtschaftsentwicklung

Zo dicht bij elkaar, maar toch heel anders. Eigendomsverhoudingen, productie en werkgelegenheid in de vier mijnbouwgebieden in het Maas-Rijngebied - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2016)
Keywords: Arbeitsmarkt; Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer; Grenzgebiet; Steinkohlenbergbau

Europäische Integration und Europa der Regionen. Überlegungen zur Geschichte der grenzüberschreitenden Zusammenarbeit in den Beziehungen Belgiens und Nordrhein-Westfalens - Brüll, Christoph (Geschichte im Westen, 2015)
Keywords: Europäische Integration; Grenzüberschreitende Kooperation; Nordrhein-Westfalen

Pierre Nothomb, het comité de politique nationale en de Belgische annexionistische campagne tijdens en na de Eerste Wereldoorlog - Waele, Maria de (Studies over De Sociaaleconomische Geschiedenis Van Limburg/Jaarboek Van Het Sociaal Historisch Centrum Voor Limburg, 2015)
Keywords: Annexion; Erster Weltkrieg; Nothomb, Pierre (1887–1966); Versailler Vertrag (1919)

Changing Border Regimes. Mining, and Cross-border Labor in the Dutch–Belgian–German Borderlands, 1900–1973 - Knotter, Ad (Journal of Borderlands Studies, 2014)
„In this article the incidence of cross-border commuting to the mining districts in the Belgian–Dutch–German borderlands, known today as the Euregion Meuse-Rhine, will be related to the impact of state borders in different periods. Cross-border labor was closely related to changing border regimes based on uneven economic development, (un)familiarity, and the policy impact of powerful institutions like the state and the church. The main argument is that after the First World War in Dutch Limburg a conscious policy to control the labor force and bind them to mining in the region was relatively successful. Discrepancies in wages and employment opportunities led to border-crossing during restricted periods and for specific groups of workers only.“
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Living on the edge. Comparative research on German, Belgian and Dutch border towns at war (1914–1919) - Liemann, Bernhard (Grenzfälle: Transfer und Konflikt zwischen Deutschland, Belgien und den Niederlanden im 20. Jahrhundert, 2013)
Keywords: Erster Weltkrieg; Eupen; Grenzstadt; Roermond; Tongern

The impact of boundaries on cross-border mobility and migration in the Liège-Limburg area (19th–20th centuries) as retrieved from population records - Rutten, Willibrord (Internationales Archivsymposion in Luxemburg (2012). Grenzüberschreitende Migration und Archive. Annalen, mit einem Nachtrag zum Symposion Lüttich (2011) Erster Weltkrieg, 2013)
Keywords: Grenzarbeitnehmer; Steinkohlenbergbau

Liefde met en zonder grenzen. De geografische horizon van huwelijkspartners in Limburg in de negentiende en vroege twintigste eeuw - Ekamper, Peter; Poppel, Frank van (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2012)
Keywords: Binationale Ehe; Binationales Ehepaar; Ehepaar; Kulturkontakt; Provinz Limburg (Niederlande)

Small towns in the Great War. German, Belgian and Dutch perspectives from the border region compared (1914–1919) - Liemann, Bernhard (Internationale Archivsymposien in Ede (NL) (2010) und Lüttich (B) (2011) – Annalen, 2012)
Keywords: Erster Weltkrieg; Eupen; Grenzstadt; Roermond; Tongern

Grenz-Controle, Grens-Kontrolle. Aachen, Eupen, Maastricht - oral histories - Boogard, Jac van den; Clemens, Luise; Heinen, Armin; Jantsch, Johanna; Ruland, Herbert; Schleinzer, Anika (Gardez!-Verlag, 2008)
Keywords: Alltag; Dreiländereck; Grenzgebiet; Rhein-Maas-Gebiet

Inleiding. Arbeidsmigranten en grensarbeiders. Vergelijkende perspectieven op de mijnarbeidsmarkten in het Belgisch-Duits-Nederlandse grensgebied in de twintigste eeuw - Knotter, Ad (TSEG - The Low Countries Journal of Social and Economic History, 2008)

Regional labour markets and international migration in twentieth-century Europe. The cases of coal mining in Liège (B) and Limburg (NL) compared - Langeweg, Serge; Roels, Leen; Knotter, Ad (Mitteilungsblatt des Instituts für Soziale Bewegungen. Forschungen und Forschungsberichte, 2008)
Keywords: Arbeitsmarkt; Arbeitsmigration; Grenzarbeitnehmer; Lüttich; Steinkohlenbergbau; Südlimburg (Niederlande)

Trekarbeiders en pendelaars. Grensarbeid in oostelijk Zuid-Limburg, 1875–1914 - Langeweg, Serge (Zestig jaar vorsen in de geschiedenis. Jubileumboek Het Land van Herle 1945–2005, 2006)
Keywords: Arbeitsmigration; Grenzarbeitnehmer; Südlimburg (Niederlande)

De bunkers van de grensstelling langs de Limburgse kanalen (1934–1940) - Janssen, Erik (België onder de wapens, 2005)
Keywords: Befestigung; Kanal; Militär; Zweiter Weltkrieg

The Maas-Rhine Euroregion. A Laboratory for European Integration? - Knippenberg, Hans (Geopolitics, 2004)
„The transborder and trilingual Maas–Rhine Euroregion is often presented as a laboratory for European integration. The authorities in the region promote the image of a region that has ‘always’ been a unity, but which is divided by artificial boundaries – ‘scars of history’ – as a result of power politics. In this essay this image is confronted with the reality of the cross-border interactions and identities of the people involved. This confrontation leads to the conclusion that although there is political, economic and cultural cooperation in the region, the region is not at all politically, economically and culturally integrated. The national border as a physical barrier may have been removed, but the economic, social, juridical and cultural barriers are still there. The unification and integration of the citizens living in the region is being impeded by conflicting national systems of law and regulations, by communication and information media focused on national issues, by nationally oriented infrastructure, and especially by strongly different national cultures and identities. The consequences for European integration in general are analysed by comparing this regional integration with the national integration and nation-building policies of the past.“
Keywords: Euregio Maas-Rhein; Europäische Integration; Grenzüberschreitende Kooperation

Grenzen-Los, Grenzen-Loos, Sans-Frontières - zu Gegenwart und Perspektiven grenzüberschreitender politisch-historischer Bildung am Dreiländereck Belgien, Deutschland, Niederlande - Ruland, Herbert (Grenzen überschreiten - Netze bilden. Nutzen und Kosten für die Erwachsenenbildung. Dokumentation der 45. Salzburger Gespräche für Leiterinnen und Leiter in der Erwachsenenbildung / Pädagogische Arbeits- und Forschungsstelle des Verbandes Österreichischer Volkshochschulen, 2003)
Keywords: Dreiländereck; Politische Bildung

The border paradox. Uneven development, cross-border mobility and the comparative history of the Euregio Meuse-Rhine - Knotter, Ad (Fédéralisme Régionalisme, 2002)
Keywords: Euregio Maas-Rhein; Grenzverkehr

Historische interacties in de Euregio Maas-Rijn. Migratiestromen in een grensgebied - Korres, Achim (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer

Paradoxen van de grens. Ongelijke ontwikkeling, grensoverschrijdende mobiliteit en de vergelijkende geschiedenis van de Euregio Maas-Rijn - Knotter, Ad (Studies over de sociaal-economische geschiedenis van Limburg - Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2001)
Keywords: Euregio Maas-Rhein; Grenzverkehr

„Das Loch im Westen“ - Ein Schmuggelparadies - Trees, Wolfgang (Deutschland - Niederlande. Heiter bis wolkig. [Begleitbuch zur Ausstellung im Haus der Geschichte der Bundesrepublik Deutschland, Bonn, 22. November 2000 bis 16. April 2001 und im Rijksmuseum, Amsterdam, 26. Mai bis 16. September 2001], 2000)
Keywords: Aachen (Region); Herzogenrath; Kerkrade; Schmuggel; Vaals